Novel switching method for single-phase NPC three-level inverter with neutral-point voltage control - Lee, June Seok; Lee, Seung Joo; Lee, Kyo Beum (International Journal of Electronics, 2018)
This paper proposes a novel switching method with the neutral-point voltage control in a single-phase neutral-point-clamped three-level inverter (SP-NPCI) used in photovoltaic systems. A proposed novel switching method for the SP-NPCI improves the efficiency. The main concept is to fix the switching state of one leg. As a result, the switching loss decreases and the total efficiency is improved. In addition, it enables the maximum power-point-tracking operation to be performed by applying the proposed neutral-point voltage control algorithm. This control is implemented by modifying the reference signal. Simulation and experimental results provide verification of the performance of a novel switching method with the neutral-point voltage control.
Keywords: Maximum Power Point Tracking; Neutral point clamped inverters; Neutral point voltage control; Neutral-point clamped three-level inverter; NPC three- level inverters; Photovoltaic systems; Single phase; Three-level inverters; natural-point voltage control; neutral-point-clamped inverter; pulse-width modulation method; Single-phase; three-level inverter